1997
DOI: 10.1136/oem.54.9.662
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene-albumin adducts in humans exposed to polycyclic aromatic hydrocarbons in an industrial area of Poland.

Abstract: (SEM 0.296), respectively) than in the winter samples (3.06 fmol adducts/pg albumin (SEM 0.187) and 3.04 fmol adducts/Ig albumin (SEM 0.184), respectively) even though the air measurements showed higher concentrations of PAHs in the winter. The statistical analysis did not show any effects of air exposures on concentrations of BPDE-albumin adduct. Conclusions-A multiple regression analysis of the measured concentrations of BPDE-albumin adducts for all the groups, during both seasons, indicates that occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The finding of an increase in BPDE-Alb adducts in workers due to exposure to COE in present study is consistent with other investigations,3436 although Omland et al 37 and Kure et al 38 showed no statistical significance in the levels of B a P-albumin adducts between the exposed and control groups and no contribution of occupational exposure to COE to the formation of adducts. In addition, some results from other studies also showed that the BPDE protein adducts in workers exposed to COE were not affected by smoking,34 37 39 probably because the exposure to COE in coke oven workers is overwhelmingly high compared with exposure to smoking.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of an increase in BPDE-Alb adducts in workers due to exposure to COE in present study is consistent with other investigations,3436 although Omland et al 37 and Kure et al 38 showed no statistical significance in the levels of B a P-albumin adducts between the exposed and control groups and no contribution of occupational exposure to COE to the formation of adducts. In addition, some results from other studies also showed that the BPDE protein adducts in workers exposed to COE were not affected by smoking,34 37 39 probably because the exposure to COE in coke oven workers is overwhelmingly high compared with exposure to smoking.…”
Section: Discussionsupporting
confidence: 92%
“…Personal exposures to B[a]P in this study were 2 or 3 times higher than in the former study (6). Kure et al (11) analyzed benzo[a]pyrene diolepoxide (BPDE)-albumin adducts in coke oven workers. They found no difference between exposed and control groups.…”
mentioning
confidence: 74%
“…In all three studies that determined the effect of exposure to PAHs in coke oven workers (11), to nitroPAHs in bus garage workers (21), or to epichlorohydrin in factory workers (40), no effects of exposure on these protein adducts were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations